Avaliação do efeito do LASSBio-596, um análago da talidomida, na angiogênese inflamatória em córnea de coelho - Ribeiro, João Crispim Moraes Lima (2011)
There is exacerbation of the angiogenic process in various diseases, especially in corneal neovascularization. For the treatment of these diseases, several drugs were studied with antiangiogenic properties. The aim of this study was to evaluate the effect of LASSBio-596, structurally designed as a hybrid of thalidomide, sildenafil and arilsulfonamide, on inflammatory corneal angiogenesis. Eighteen rabbits were submitted to an alkaline cauterization in the right cornea. The animals were randomly allocated in three groups: vehicle, dexamethasone, and LASSBio-596 group. Drugs were administrated by eye drops three times per day for 21 days. Evaluations were performed on days 3, 6, 9, 12, 15, 18, and 21 post-cauterization. At these time points, digital images of the cornea were captured in a standard fashion. Angiogenic response was measured using software that was developed specifically for this purpose. It calculated the following parameters: neovascularization area (NA), total vascular length (TVL), and blood vessel number (BVN). It was observed that dexamethasone significantly decreased NA, TVL, and BVN during all assessments. From NA it was calculated the angiogenesis rate (AR) in each group. Therefore, dexamethasone completely inhibited the inflammatory corneal angiogenesis with angiogenesis rate (AR) of -0.001 ± 0.006 mm2/day, which was significantly lower (p < 0.001) than that observed after treatment with vehicle (0.078 ± 0.024 mm2/dia) and LASSBio-596 (0.054 ± 0.012 mm2/dia). Although LASSBio-596 reduced angiogenesis in relation to vehicle, according to NA, TVL and BVN values, this difference was not statistically significant. However, it was found that the AR as measured in the LASSBio-596 group was significantly lower (p < 0.05) than that seen in control animals, indicating a potential antiangiogenic effect. We conclude that topical application of LASSBio-596 at 1.0% has a partial inhibitory effect on inflammatory corneal angiogenesis in rabbits.